Quantification of Process Operability Using Flexibility Analysis - Zhao, Fei; Mei, Chentao; Zhu, Lingyu; Chen, Xi (Computer Aided Chemical Engineering, 2023)
Industrial plants are commonly subject to uncertainties during operation. Operability and flexibility are two key properties for design models with uncertain parameters. In this study, flexibility analysis is first considered, where a derivative-free optimization method based on flexibility index is designed to identify the largest rectangular flexibility space, while the optimal nominal point of uncertain parameters can be obtained. Then, a novel operability analysis method is proposed to quantify the entire system operability. Based on the critical points of uncertainties in the flexibility space, a line projection method is adopted to locate boundary points of the operational space. The volume of the operational space is calculated by the Delaunay Triangulation method, and the ratio to the physical operational ranges can be used to assess the system operability. The case study shows the proposed method is capable of dealing with the nonconvex operational spaces.